Upaya Meningkatkan Ketrampilan Membaca Siswa dengan Penggunaan Media Kartu Kata pada Pembelajaran Bahasa Indonesia Kelas III SD Negeri Jurang Mangu Barat 03 - Zuliani, Rizki; Apriola, Nabilla Putri; Fathya, Nisrina Nur (Lembaga Yasin AlSys, 2023)
This research was motivated by the low reading skills of students in class III Indonesian language learning at SDN JURANG MANGU BARAT 03. The method for overcoming this problem is to apply a special Classroom Action Research model, namely by using word card media to find out and deal with learning to read problems start. When the research was carried out in February 2018. Data collection techniques were tests, observation, documentation. The results of this study can be concluded that from several types of teacher efforts it is felt that there is an increase for students, both in the academic and non-academic fields. However, in the academic field it turns out that they have not been able to meet the expectations as stated in the indicators, because according to the results of the teacher's observations of students, they do not fully have reading skills according to the standards given. Based on the analysis used to test the hypothesis that the use of word card media in Indonesian lessons can improve the reading skills of Grade III students at SD Negeri Jurang Mangu Barat 03, South Tangerang City. The use of word card media in Indonesian lessons can improve student achievement in Class III SD Negeri Jurang Mangu Barat 03 Kota Tangerang Selatan for the 2017/2018 academic year with an average score of 82.31 out of 22 students.